Risking Antimicrobial Resistance A collection of one-health studies of antibiotics and its social and health consequences - Jensen, Carsten Strøby; Nielsen, Søren Beck.; Fynbo, Lars.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
Antimicrobial resistance (AMR) is predicted to be one of the greatest threats to public health in the twenty-first century. In this context, understanding the reasons why perceptions of antibiotic risk differ between different groups is crucial when it comes to tackling antibiotic misuse. This innovative volume gathers together chapters written by sociologists, psychologists and linguists with the common aim of examining the social factors that affect use of antibiotics among humans and animals. A unique focus on Denmark - one of the world's most progressive countries when it comes to antibiotic regulation - as well as Europe more broadly, makes this book a valuable resource for regulatory deliberations on future antibiotic policy to effectively combat AMR.
Chapter 1 Risking Antimicrobial Resistance - A one-health study of antibiotic use and its societal aspects -- Chapter 2 Dealing with explicit patient demands for antibiotics in a clinical setting -- Chapter 3 Antibiotics in France and Italy: A linguistic analysis of policies and practices compared to Danish standards -- Chapter 4 Talk on cough: symptom, sign and significance in acute primary care -- Chapter 5 To prescribe or not to prescribe' is not the only question: Physician attitudes towards antibiotics and prescription practices in Spain -- Chapter 6 Governing the consumption of antimicrobials: The Danish model for using antimicrobials in a comparative perspective -- Chapter 7 My Life as a Pig: MRSA and the Control of Life in Contemporary Pig Production -- Chapter 8 Social stigmatization of pig farmers: Medical perspectives on modern pig farming -- Chapter 9 What is 'good doctoring' when antibiotic resistance is a global threat? -- Chapter 10 Governing risk by conveying just enough (un-)certainty: Rearticulating good doctoring as a psy-medical competence -- Chapter 11 The antibiotic challenge: justifications for antibiotic usage in the world of medicine -- Chapter 12 Concluding remarks on 'Risking Antimicrobial Resistance'.
Keywords: Science -- Social aspects; Social medicine; Medicine, Preventive; Health promotion; Clinical health psychology; Social sciences -- Philosophy; Science and Technology Studies; Medical Sociology; Health Promotion and Disease Prevention; Health Psychology; Social Theory